Post-stroke delirium is a predictor of prolonged hospital stay and poor functional outcome at 3 months - Boudiba, Yacine; Gens, Robin; Ourtani, Anissa; De Backer, Gaël; Guldolf, Kaat; Vandervorst, Fenne; De Raedt, Sylvie (Frontiers in Stroke, 2026)
BackgroundDelirium is a frequent complication of acute ischemic stroke associated with poor outcome. The complex interplay with post-stroke infections remains to be elucidated. Our study aimed to investigate whether post-stroke delirium (PSD) was a predictor of prolonged hospital stay, poor functional outcome, and mortality after acute ischemic stroke, independent of the development of post-stroke pneumonia (PSP) and post-stroke urinary tract infections (PSU).MethodsIn a previously published dataset of 514 patients with acute ischemic stroke, 201 patients (39%) developed delirium within the first week after stroke onset using a chart review method based on the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition criteria. Fifteen percent developed PSP and 22% PSU, using the modified criteria of the US Centers for Disease Control and Prevention. Logistic regression analyses were used to identify predictors of prolonged hospital stay (>median 9 days), poor functional outcome (modified Rankin Scale >2), and mortality at 3 months after stroke onset.ResultsMultiple logistic regression analysis showed that PSD was a predictor of prolonged hospital stay [odds ratio (OR): 4.085, 95% confidence interval (CI): 2.445–6.824] and poor functional outcome [OR: 3.362, 95% CI: 1.851–6.107) at 3 months after stroke onset, even after adjustment for age, premorbid disability, National Institutes of Health Stroke Scale on admission, PSP, and PSU. PSD was no predictor of mortality after stroke.ConclusionPSD is a predictor of prolonged hospital stay and poor functional outcome at 3 months after ischemic stroke, independent of PSP and PSU.